2018
DOI: 10.1007/s12192-018-0919-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological resilience of a temperate soft coral to ocean warming and acidification

Abstract: Atmospheric concentration of carbon dioxide (CO) is increasing at an unprecedented rate and subsequently leading to ocean acidification. Concomitantly, ocean warming is intensifying, leading to serious and predictable biological impairments over marine biota. Reef-building corals have proven to be very vulnerable to climate change, but little is known about the resilience of non-reef-building species. In this study, we investigated the effects of ocean warming and acidification on the antioxidant enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Conversely, the role of host-derived antioxidants in bleaching and thermal resilience remains disputed. While pioneering studies show antioxidant activation in adult coral host tissue and larvae under heat stress (16,(25)(26)(27)(28)(29), more recent experiments have failed to find this pattern (10,22). However, the coral host control of the level of oxygen radicals and ROS is likely a major component in the dynamics of coral-algal symbiosis maintenance (18,30).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the role of host-derived antioxidants in bleaching and thermal resilience remains disputed. While pioneering studies show antioxidant activation in adult coral host tissue and larvae under heat stress (16,(25)(26)(27)(28)(29), more recent experiments have failed to find this pattern (10,22). However, the coral host control of the level of oxygen radicals and ROS is likely a major component in the dynamics of coral-algal symbiosis maintenance (18,30).…”
Section: Introductionmentioning
confidence: 99%
“…Lopes et al (2018) found GST activities in the soft coral Veretillum cynomorium did not change signi cantly under warming and acidi cation. The GST activity in our experiment signi cantly decreased under pH 7.3, indicating that extreme low pH disrupted the balance of GST.…”
mentioning
confidence: 88%
“…A recent experimental study in Acropora millepora, a reef-building coral in the Great Barrier Reef, also found a strong antioxidant response to reduced salinity (Aguilar et al, 2019), suggesting that this response mechanism is conserved across coral genera. The upregulation of antioxidantencoding genes has been described in corals exposed to a variety of biotic and abiotic threats, including increased temperature (Barshis et al, 2013;Dixon et al, 2015), acidification (Davies et al, 2016;Lopes et al, 2018), and disease (Wright et al, 2015(Wright et al, , 2017Daniels et al, 2015).…”
Section: Oxidative Stress In the Coral Hostmentioning
confidence: 99%